PRMT1 is an important factor for medulloblastoma cell proliferation and survival - Gu, Xiao; He, Miao; Lebedev, Timofey; Lin, Cheng-Han; Hua, Zhong-Yan; Zheng, Y. George; Li, Zhi-Jie; Yang, Jer-Yen; Li, Xing-Guo (Biochemistry and biophysics reports, 2022)
Aberrant expression of protein arginine methyltransferases (PRMTs) has been implicated in a number of brain tumors, but the role of PRMT1 in medulloblastoma, the most common malignant pediatric brain tumor, remains unexplored. By examining the publicly available databases of pediatric brain tumor collection, we found that PRMT1 was predominantly expressed in medulloblastomas across all the pediatric brain tumors and that the high-level expression of PRMT1 correlated with poor survival of medulloblastoma patients. To determine the role of PRMT1 in medulloblastoma cells, we established an inducible knockdown system and demonstrated that PRMT1 depletion decreased medulloblastoma cell proliferation and induced cell apoptosis. Furthermore, the diamidine compounds, previously shown to exhibit selective PRMT1 inhibition, suppressed medulloblastoma cell viability in a dose-dependent manner. Finally, we observed induction of medulloblastoma cell apoptosis by the potent diamidine compounds at low micromolar concentrations. Together, our results suggest that PRMT1 could be an actionable therapeutic target in medulloblastoma. •PRMT1 is predominantly expressed in medulloblastoma among pediatric brain tumors and correlates with poor patient survival.•PRMT1 knockdown suppressed medulloblastoma cell growth and induced apoptosis.•The diamidine compounds reduced medulloblastoma cell viability and induced medulloblastoma cell apoptosis.